Challenges and solutions in implementing electronic prescribing in Iran’s health system: a qualitative study - Neda Borhani Moghani; Elahe Hooshmand; Marzie Zarqi; Marziyhe Meraji (BMC Medical Informatics and Decision Making)
Abstract Background The use of electronic prescribing is recognized as a strategic tool for improving healthcare. Given the nationwide implementation of electronic prescribing systems initiated in 2020, this study aims to explore the challenges and solutions for implementing electronic prescribing in Iran’s health system as a developing country. Methods This qualitative study was conducted through interviews with physicians, pharmacy staff, and electronic prescribing representatives in 2023. Initially, three in-depth interviews were conducted to develop the interview questions, resulting in three separate interview guides for each participant group (supplementary file no.1). Participants were purposively selected, including 12 physicians, 15 electronic prescribing representatives, and 9 pharmacy staff members. Interviews continued until data saturation was reached. The interviews were recorded, transcribed, and analyzed using Inductive content analysis with MAXQDA version 10 software. To identify challenges, sessions were held, and a final list of challenges was categorized. In the final stage, expert panels including 3 researchers, 4 e-prescribing representatives, and 3 insurance experts were formed to propose solutions. Result The challenges identified in this study were categorized into two main domains: “Organizational Challenges” and “Systemic Challenges.” Organizational challenges included issues related to insurance (16 cases), patient referrals (4 cases), stakeholder education and communication (6 cases), and supervision (8 cases). Systemic challenges included infrastructure problems (18 cases), user interface (UI) issues (14 cases), and database issues (10 cases). The primary challenges in implementing electronic prescribing were system downtime and sluggishness, internet connectivity issues, and the existence of multiple insurance systems. Expert panel discussions resulted in proposed solutions, including the uniform design of software by the Ministry of Health, the establishment of an integrated electronic referral system, conducting practical training sessions for physicians, and implementing electronic signatures. Conclusion Electronic prescribing in Iran is still in its early stages and will inevitably face challenges and problems. Continuous monitoring of electronic prescribing systems is essential to address implementation issues promptly. Issues related to training insurance monitoring the user interface and database infrastructure were challenging. Overall, improvements in infrastructure, integration of insurance systems, implementation of electronic signatures, adherence to electronic prescribing standards, and provision of practical training are recommended.